Transplatin is cytotoxic when photoactivated: enhanced formation of DNA cross-links - Heringova, Pavla; Woods, Julie; Mackay, Fiona S; Kasparkova, Jana; Sadler, Peter J; Brabec, Viktor (Journal of medicinal chemistry, 2006)
It is well-known that although cisplatin, [cis-[PtCl2(NH3)2], is an anticancer drug, its isomer transplatin is not cytotoxic. Here we show that transplatin is almost as cytotoxic as cisplatin when treated cells (human keratinocytes HaCaT and ovarian cancer A2780 cells) are irradiated with UVA light (50 min, 1.77 mW cm-2). Chemical studies show that light activates both chloride ligands of transplatin, and experiments on pSP73 plasmid DNA and a 23 base-pair DNA duplex show that irradiation can greatly enhance formation of interstrand cross-links and of DNA-protein cross-links (which are not formed in the dark). Comet assays showed that UVA irradiation of transplatin-treated cells resulted in an increased inhibition of H2O2-induced DNA migration, supporting the conclusion that the cytotoxicity of photoactivated transplatin is mainly due to formation of DNA interstrand and DNA-protein cross-links.
Keywords: kometový test; poškození DNA; Stereoisomerism; Magnetic Resonance Spectroscopy; protinádorové látky; stereoizomerie; kultivované buňky; Cross-Linking Reagents; Humans; cisplatina; DNA Damage; keratinocyty; Antineoplastic Agents; Female; magnetická rezonanční spektroskopie; Cells, Cultured; ženské pohlaví; Ultraviolet Rays; DNA Footprinting; DNA; Proteins; Comet Assay; DNA footprinting; proteiny; ultrafialové záření; Keratinocytes; lidé; Cisplatin; nádory vaječníků; Ovarian Neoplasms; reagencia zkříženě vázaná